Risk Factors of Bone Mass Loss at the Lumbar Spine: A Longitudinal Study in Healthy Korean Pre- and Perimenopausal Women Older than 40 Years. - Sungsu Kim; Jaehoon Jung; Jung Hwa Jung; Soo Kyoung Kim; Rock-Bum Kim; Jong Ryeal Hahm (PLoS ONE, 2015)
Longitudinal studies on bone mass decline for healthy women are sparse. We performed a retrospective longitudinal study to evaluate the factor associated with bone mass changes at the lumbar spine in healthy Korean pre- and perimenopausal women over the age of 40. We examined the relation of blood tests including thyroid function tests at baseline and follow-up to the annual percentage changes in average BMD of L2-L4 (A%ΔLSBMD). Four hundred and forty-three subjects without diseases or medications pertaining to bone metabolism were analyzed. The mean A%ΔLSBMD in these subjects was -0.45%/year. Though a significant correlation was observed between the A%ΔLSBMD and age, serum thyroid-stimulating hormone (TSH) level, total cholesterol (TC) level, low-density lipoprotein cholesterol (LDL-C) level, and estimated glomerular filtration rate (eGFR) at baseline and follow-up, there was a weak correlation between A%ΔLSBMD and these variables. From multiple linear regression analyses, the percent body fat, age, serum TSH level, serum uric acid level, and the menopause at follow-up were showed to have a significant association with the A%ΔLSBMD. Unlike age, percent body fat, and menopause at follow-up, which had a negative association with the A%ΔLSBMD, serum TSH level and serum uric acid level, had a positive association with the A%ΔLSBMD. The results from our study showed that the notable risk factors of BMD loss at the lumbar spine in population of our study were advancing age, menopause, higher percent body fat, lower normal TSH, and lower serum uric acid levels.